Investigation of Cyber Crime by the Rescret Sat to Improve Crime Clearance at Cimahi Police - sinaga, Giosian Yohanes (Indonesian Journal of Police Studies, 2024)
Misuse of information and communication technology by utilizing computers as a mode of operation is called cybercrime. Cybercrime criminal acts in Indonesia have been regulated in ITE Law Number 11 of 2008 concerning Information and Electronic Transactions. The number of cybercrime crimes in Cimahi Regional Police has increased from 2017 to 2019. Cimahi Regional Police as one of the Republic of Indonesia's National Police institutions has the task of maintaining security and order, providing protection, containment and services to the community, and enforcing the law in accordance with Article 14 paragraph (1) letter g of Law No. 2 in 2002. This study aims to describe cybercrime criminal offenses in the Cimahi Regional Police jurisdiction, including the handling and factors that influence the handling of cybercrime criminal offenses by the Cimahi District Criminal Investigation Unit. The research method uses a qualitative approach, with data collection techniques through interviews, observation, and documentation. The results of this study indicate that the investigation of cybercrime crimes by the Cimahi Police Criminal Unit Cyber ​​Unit, carried out in accordance with the investigation mechanism with planning, management, operation and control by utilizing information technology such as television, social media, and the Victim's HP CDR. The most common cases are online fraud and fraud, increasing cybercrime cases are not comparable with crime clearance. Factors that influence the handling of cybercrime crime are internal factors including lack of human resources, work performance, collaboration with relevant agencies and supporting equipment. Meanwhile, external factors include the lack of public understanding of cyber crime, evidence and socialization.